Register in User Experience Articles from Nielsen Norman Group (Nngroup.Com) - Addina, Fara Ruby (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
Depending on the setting, language can vary according to the register. Convention, which people are partly required to follow, establishes it. For instance, the vocabulary used to discuss something with coworkers or professionals will differ from that used with family members. Abbreviations are used to communicate precisely in different contexts. This study aims to describe the types of registers used in the user experience (UX) filed by Nielsen Norman Group. The data is qualitatively analyzed. Each term found in the sample that can be considered a register will be grouped into kinds of word formation, dimensions of register, and functions of register. The results show that there are 11 compound words and two abbreviations. According to Pateda’s classification of the functions of the register, it can be said that seven of eight articles apply the oratorical (frozen) function, as these articles tell the audience how to do something in the right way. This study proved that the User Experience field also has its own register. Some words and phrases tend to be used among User Experience practitioners only.